2007
DOI: 10.1111/j.1399-5448.2007.00266.x
|View full text |Cite
|
Sign up to set email alerts
|

The transition to young adulthood in youth with type 1 diabetes on intensive treatment

Abstract: These data suggest that youth who begin intensive treatment as adolescents generally have good metabolic and psychosocial outcomes as young adults. However, those who have high levels of depressive symptoms in adolescence tend to continue to have such symptoms in early adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 27 publications
9
76
0
4
Order By: Relevance
“…For instance, a prospective study that aimed to assess the impact on the QoL over 5 years in a cohort of 117 diabetic patients showed that despite the damage on metabolic control, the QoL did not change over time. 27 The reasons for the improvement of HbA1c and absence of HRQoL remain open for discussion. Organization of care, stricter guidelines, more education, length of follow-up, a more active role of children and adolescents themselves, and the socioeconomic level of their parents may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a prospective study that aimed to assess the impact on the QoL over 5 years in a cohort of 117 diabetic patients showed that despite the damage on metabolic control, the QoL did not change over time. 27 The reasons for the improvement of HbA1c and absence of HRQoL remain open for discussion. Organization of care, stricter guidelines, more education, length of follow-up, a more active role of children and adolescents themselves, and the socioeconomic level of their parents may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one may speculate whether implementation of CGM from the onset of clinical disease may have an especially positive effect in the adolescent patient cohort independent of glycaemic control as seen in the present study. Moreover, imperfect adherence with long-term diabetes management has been recognised as a limitation to achieve good metabolic control in adolescents and young adults [15][16][17]. Taken together, the rapid introduction of continuous glucose monitoring into diabetes treatment may be helpful and effective from both metabolic and educational aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the harm caused for metabolic control, QoL did not change over time, at a 95% confidence interval (22) .…”
Section: Qol and Socio-demographic Factorsmentioning
confidence: 99%